2016
DOI: 10.1007/s00127-016-1329-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender discrimination, educational attainment, and illicit drug use among U.S. women

Abstract: Purpose While gender inequality has been a topic of concern for decades, little is known about the relationship between gender discrimination and illicit drug use. Further, whether this association varies by education level is unknown. Methods Among 19,209 women participants in Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (2004–2005), we used logistic regression to test the association between gender discrimination (measured with four items from the Experiences of Discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
3
9
0
1
Order By: Relevance
“…In this study, we found that sexism was bivariately associated with greater psychological distress, alcohol-related consequences, and drug-related consequences in a sample of gender-diverse SMW, consistent with our Hypothesis 1 and with existing literature among women more broadly (Carliner et al, 2017;Klonoff et al, 2000;Ro & Choi, 2010;Swim et al, 2001;Zucker & Landry, 2007). This is among the first studies to test the association between SMW's sexism and the extent to which SMW's alcohol and drug use caused any negative consequences.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that sexism was bivariately associated with greater psychological distress, alcohol-related consequences, and drug-related consequences in a sample of gender-diverse SMW, consistent with our Hypothesis 1 and with existing literature among women more broadly (Carliner et al, 2017;Klonoff et al, 2000;Ro & Choi, 2010;Swim et al, 2001;Zucker & Landry, 2007). This is among the first studies to test the association between SMW's sexism and the extent to which SMW's alcohol and drug use caused any negative consequences.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the relationship between gender and educational level, women and men with low educational level started cocaine use much earlier than those with secondary studies. This is particularly important to women with primary education, since they could have a higher risk of gender discrimination and illicit drug use 27 . However, the age at onset of cocaine use and the development of CUD is still earlier in men compared to women who have a low educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted with an adolescent population, the authors observed that educational achievements had very important weight in the progression towards substance use disorders 26 . Furthermore, gender discrimination has been consistently associated with the use of illicit drugs and substance use disorders among women in the US, with those with an educational level below secondary occupying a position of greater risk 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Most research on gender discrimination and health has focused on psychological health in women and sex differences in frequency, perception, and sequelae [1619]. However, the potential effects of perceived gender discrimination on physical health, including CVD, have received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%